2014
DOI: 10.1093/rheumatology/keu358
|View full text |Cite
|
Sign up to set email alerts
|

Impact of inadequate adherence on response to subcutaneously administered anti-tumour necrosis factor drugs: results from the Biologics in Rheumatoid Arthritis Genetics and Genomics Study Syndicate cohort

Abstract: Objective. Non-adherence to DMARDs is common, but little is known about adherence to biologic therapies and its relationship to treatment response. The purpose of this study was to investigate the association between self-reported non-adherence to s.c. anti-TNF therapy and response in individuals with RA.Methods. Participants about to start s.c. anti-TNF therapy were recruited to a large UK multicentre prospective observational cohort study. Demographic information and disease characteristics were assessed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 20 publications
7
82
1
1
Order By: Relevance
“…33,35 More recently, Waimann et al 36 found that adherence to oral disease-modifying antirheumatic drugs and corticosteroid therapy in patients with RA was low, ranging from 58% to 71%, with only one fifth of patients showing greater than 80% adherence. Recently, Bluett et al 37 reported nonadherence with biological therapy in 57 (20%) of 286 patients. Also, it has been reported that 21% to 35% of patients who are administered anti-TNF therapy discontinue within their first year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…33,35 More recently, Waimann et al 36 found that adherence to oral disease-modifying antirheumatic drugs and corticosteroid therapy in patients with RA was low, ranging from 58% to 71%, with only one fifth of patients showing greater than 80% adherence. Recently, Bluett et al 37 reported nonadherence with biological therapy in 57 (20%) of 286 patients. Also, it has been reported that 21% to 35% of patients who are administered anti-TNF therapy discontinue within their first year of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A study into self-reported adherence to self-injectable TNFIs in rheumatoid arthritis patients found that 27% of patients had not taken the drug on the scheduled date on at least one occasion in the first 6 months of therapy (Bluett et al, 2014). Crucially, this was associated with a lower measured response following 6 months of therapy, suggesting that non-adherence may play a role in the loss of effectiveness of biologic therapies.…”
Section: Probable Factors Accounting For Survival With Biologicsmentioning
confidence: 99%
“…However, the long-term efficacy of these medications is directly dependent upon the degree of patient compliance and medication adherence. 1 While usually welltolerated, most biologic agents are injectable drugs. The subcutaneous injections can be painful, and fear of the needle can be a real issue, and may even prevent some patients from undergoing treatment with a biologic agent.…”
Section: Original Researchmentioning
confidence: 99%